Screening of transporters to improve xylodextrin utilization in the yeast Saccharomyces cerevisiae. - Chenlu Zhang; Ligia Acosta-Sampson; Vivian Yaci Yu; Jamie H D Cate (PLoS ONE)
The economic production of cellulosic biofuel requires efficient and full utilization of all abundant carbohydrates naturally released from plant biomass by enzyme cocktails. Recently, we reconstituted the Neurospora crassa xylodextrin transport and consumption system in Saccharomyces cerevisiae, enabling growth of yeast on xylodextrins aerobically. However, the consumption rate of xylodextrin requires improvement for industrial applications, including consumption in anaerobic conditions. As a first step in this improvement, we report analysis of orthologues of the N. crassa transporters CDT-1 and CDT-2. Transporter ST16 from Trichoderma virens enables faster aerobic growth of S. cerevisiae on xylodextrins compared to CDT-2. ST16 is a xylodextrin-specific transporter, and the xylobiose transport activity of ST16 is not inhibited by cellobiose. Other transporters identified in the screen also enable growth on xylodextrins including xylotriose. Taken together, these results indicate that multiple transporters might prove useful to improve xylodextrin utilization in S. cerevisiae. Efforts to use directed evolution to improve ST16 from a chromosomally-integrated copy were not successful, due to background growth of yeast on other carbon sources present in the selection medium. Future experiments will require increasing the baseline growth rate of the yeast population on xylodextrins, to ensure that the selective pressure exerted on xylodextrin transport can lead to isolation of improved xylodextrin transporters.